Reciprocal Cooperation of Type A Procyanidin and Nitrofurantoin Against Multi-Drug Resistant (MDR) UPEC: A pH-Dependent Study - Vasudevan, Sahana; Thamil Selvan, Gopalakrishnan; Bhaskaran, Sunil; Hari, Natarajan; Solomon, Adline Princy (Frontiers in Cellular and Infection Microbiology, 2020)
Uropathogenic E. coli (UPEC) accounts for the majority of complicated and uncomplicated urinary tract infections. The use of phytomolecules in the treatment of UTI is fast gaining attention. The current report identifies a multidrug-resistant strain (QSLUPEC7) which is a strong biofilm producer, among the considered clinical isolates. The antimicrobial and antibiofilm activity were evaluated for the phytomolecule, Type A procyanidin (TAP) from Cinnamomum zeylanicum against QSLUPEC7. TAP treatment did not affect the growth of the MDR strain but affected the biofilm formation (~70% inhibition). The confocal microscopic examination reveals the biofilm inhibition and the live cells in the biofilm corroborates the antimicrobial results. Further, the synergy studies of TAP and nitrofurantoin (NIT) were carried at different pH. TAP acts synergistically with nitrofurantoin at different pH considered. A closer look in the results reveals that at pH 5.8, maximum growth inhibition is recorded. The gene expression analysis shows that TAP alone and in combination with NIT downregulates the major fimbriae adhesins of UPEC. The results conclude that the TAP has an antibiofilm activity against the multidrug-resistant strain of UPEC, without affecting the growth. Also, TAP reciprocally cooperates with nitrofurantoin at different pH by downregulating the adhesins of UPEC.